Smart and intelligent systems : the human elements in artificial intelligence, robotics, and cybersecurity - Moallem, Abbas (The human element in smart and intelligent systems, 2022)
"This book is perfect for engineering students in data sciences, artificial intelligence, practitioners at all levels in the field of human factors and ergonomics, systems engineering, computer science, software engineering and robotics"--